Polarization of Muslim Voters in the 2024 Regional Elections in North Maluku - Aji Deni (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
Political polarization among Muslim voters in the 2024 Regional Elections (Pilkada) in North Maluku is a complex phenomenon shaped by the legacy of historical conflicts (1999–2002), religious identity, and colonial power structures. This study aims to analyze 18 dimensions of polarization across 10 regencies/cities in North Maluku and examine whether electoral preference differences are primarily driven by ideological factors or pragmatic considerations. Employing an exploratory qualitative approach, the study combines a Likert-scale survey (60 Muslim respondents), in-depth interviews with 10 key informants (academics, religious leaders, and politicians), and secondary document analysis. The theoretical framework includes political polarization theories in elections, particularly those highlighting the relationship between religious authority and political power as well as the role of historical trauma in shaping political loyalty. The findings reveal that political polarization in North Maluku is largely influenced by ethno-religiohistorical factors, such as the electoral dominance of the historical sultanate, whose authority has been eroding, and the society’s deep-rooted attachment to collective memories of past conflicts. Contrary to global polarization patterns often driven by economic or class-based ideological divides, economic factors have a limited impact in this context, indicating a phenomenon of performative economism—economic rhetoric without concrete policies. Meanwhile, distrust toward political elites further deepens identity fragmentation, reinforcing the unique nature of polarization in the region. This study concludes that political polarization in postcolonial societies such as North Maluku requires a contextual approach that considers the entanglement of history, religion, and geography. Further research is recommended in other regions of Eastern Indonesia or in Southeast Asian countries with similar socio-political dynamics. Additionally, depolarization strategies based on historical reconciliation and the strengthening of inclusive political platforms should be developed to mitigate persistent identity-based tensions.